Enjambment in Thumbooâ€™s Poem â€œEvening by Batok Townâ€ - Zhiming, National University of Singapore, Bao; Luwen, National University of Singapore, Cao (Asiatic: IIUM Journal of English Language and Literature, 2013)
Enjambment is a common technique of poetry. Enjambment breaks a line at different structural points. Based on the structure of the line break, we propose four types of enjambment, and assign a severity value to them. This allows us to quantify enjambment of a stanza or poem. By examining the enjambment of Thumbooâ€™s poem â€œEvening by Batok Town,â€ we show that there is a correlation of iconicity between the nature of the imagery of a stanza and the stanzaâ€™s enjambment value.